Vascular 3D+T freehand ultrasound using correlation of doppler and pulse-oximetry data - Hennersperger, Christoph; Karamalis, Athanasios; Navab, Nassir (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2014)
We present a new system to acquire and reconstruct 3D freehand ultrasound volumes from arbitrary 2D image acquisitions over time. Motion artifacts are significantly reduced with a novel gating approach which correlates pulse oximetry data with Doppler ultrasound. The reconstruction problem is split into a ray-based sample selection on a per-scanline basis and a backward algorithm which is based on the concept of normalized convolution. We introduce an adaptive derivation of time-domain interpolation from the correlated pulse-oximetry and Doppler signals as well as an ellipsoid kernel size for spatial interpolation based on the physical resolution of the ultrasound data. We compare pulse-oximetry to classical ECG gating and further show the suitability of our normalized pulse signal for 3D+T reconstructions. The ease of use of the setup without the need of uncomfortable triggering via ECG provides the ability to use 3D+T ultrasound in every day clinical practice. © 2014 Springer International Publishing Switzerland.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 4D; adaptive; cardiac pulse phase; correlation; doppler; freehand ultrasound; reconstruction; vascular